Implementation of an electroencephalogram‐guided propofol anesthesia education program in an academic pediatric anesthesia practice. Issue 11 (20th July 2022) - Yuan, Ian; Missett, Richard M.; Jones‐Oguh, Sheri; Massa, Christopher B.; Babus, Lenard W.; Garcia‐Marcinkiewicz, Annery G.; Daly Guris, Rodrigo J.; Johnson, Gregory; McClung‐Pasqualino, Heather; Sequera‐Ramos, Luis; Iyer, Rajeev Subramanyam; Kurth, Charles D.
Abstract: Background: Propofol total intravenous anesthesia (TIVA) is increasingly popular in pediatric anesthesia, but education on its use is variable and over‐dosage adverse events are not uncommon. Recent work suggests that electroencephalogram (EEG) parameters can guide propofol dosing in the pediatric population. This education quality improvement project aimed to implement a standardized EEG TIVA training program over 12 months in a large pediatric anesthesia division. Methods: The division consisted of 63 faculty, 11 clinical fellows, 32 residents, and 28 nurse anesthetists at the Children's Hospital of Philadelphia. The program was assessed for effectiveness (a significant improvement in EEG knowledge scores), scalability (training 50% of fellows and staff), and sustainability (recurring EEG lectures for 80% of rotating residents and 100% of new fellows and staff). The key drivers included educational content development (lectures, articles, and hand‐outs), training a cohort of EEG TIVA trainers, intraoperative teaching (teaching points and dosing tables), decision support tools (algorithms and anesthesia electronic record pop‐ups), and knowledge tests (written exam and verbal quiz during cases). Results: Over 12 months, 78.5% of the division (62/79) completed EEG training and test scores improved (mean score 38% before training vs 59% after training, p < .001). Didactic lectures were given to 100% of the fellows, 100% (11/11) of new staff, and 80% (4/5 blocks) of rotating residents. Conclusion: This quality improvement education project successfully trained pediatric anesthesia faculty, staff, residents, and fellows in EEG‐guided TIVA. The training program was effective, scalable, and sustainable over time for newly hired faculty staff and rotating fellows and residents.